Rechtsstaatsförderung Handbuch für Forschung und Praxis - Kötter, Matthias 1973-; Röder, Tilmann J.; Deppe, Jens; Trappe, Julie 1972- (Verlag W. Kohlhammer, 2022)
Promoting constitutional law is an important sphere of action for German foreign and development policy. It is not a monopoly of the state, however, but is implemented by numerous organizations in Germany. The chances of a project succeeding, and also plausible assumptions about its effects, presuppose a knowledge of how to promote constitutional law that has so far not been systematically appreciated and processed, either in German-language research or in practice. This handbook fills that gap by comprehensively bringing together practical experience for the first time and linking it with the results of current legal and sociological research. The conceptual and theoretical foundations for promoting constitutional law are discussed, as are various objectives and instruments. This is based on a broad concept of promoting constitutional law that includes interfaces with other policies such as human rights, promoting democracy, promoting good governance and security sector reform.
Keywords: Durchführungsorganisationen; Entwicklungspolitik; Rechtskooperation; Rechtslinguistik; Rechtsstaatlichkeit; Rechtsstaatsaufbau; Rechtstransfer; Rechtsvergleichung; Rule of Law; Staatsaufbau